High Environmental Stability of Hepatitis B Virus and Inactivation Requirements for Chemical Biocides. (24th October 2018) - Than, Thoa Thi; Jo, Eunji; Todt, Daniel; Nguyen, Phuong Hong; Steinmann, Jochen; Steinmann, Eike; Windisch, Marc P
Abstract: Hepatitis B virus (HBV) infection is considered a major public health problem worldwide, and a significant number of reports on nosocomial and occupational outbreaks have been reported. This systematic investigation of HBV stability and susceptibility to different antiseptics revealed that HBV infectivity was very stable, with a half-life of >22 days at 37°C. At 4°C, infectivity was barely reduced for up to 9 months. Different alcohols and commercially available hand antiseptics had a virucidal effect against HBV. We propose that very strict compliance with established hygienic guidelines should be mandatory to avoid and prevent HBV infections.